The Effect of Interactive Video on Simple Positive Communication Skills of Kindergarten A2 Children at Ba Aisyiyah Dukuh Sukoharjo - Fatimah, WidaNur; Slamet, Sri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research is motivated by the problem of communication development in early child-hood. The aim of this research is to find out whether the use of interactive video media has an influence on the development of simple positive communication in Kindergarten A2 children at BA Aisyiyah Dukuh. Methodology: This type of research is quantitative research with experimental research methods. This research design uses a single-group pretest and posttest design. The subjects of this research were Kindergarten A2 children aged 4 to 5 years which amounts to 10 childrens in BA Aisyiyah Dukuh, Sukoharjo Regency for the 2023/2024 school year. Results: Based on the results of the research that has been carried out, the use of interactive video media can be used to improve the simple positive communication skills of Kindergarten A2 children at BA Aisyiyah Dukuh, as proven by hypothesis testing via the t test, obtained t = 51.430 and it is known that Sig. mark. (2-tailed) is 0.001 < 0.05, so Ho is rejected and Ha is accepted, which means there is a significant influence between interactive videos that can be used to improve the simple positive communication skills of class A2 BA Aisyiyah Dukuh children.Applications/Originality/Value: This research shows that the use of interactive video media is effective in improving communication skills in early childhood, specifically in enhancing simple positive communication. It provides valuable insights into the application of multimedia in early childhood education, offering a significant contribution to improving communication development in young learners.